2022
DOI: 10.3389/fimmu.2022.951482
|View full text |Cite
|
Sign up to set email alerts
|

The role of extravillous trophoblasts and uterine NK cells in vascular remodeling during pregnancy

Abstract: Successful embryo implantation requires both a receptive endometrium and competent blastocysts. After implantation, the maternal decidua undergoes a series of changes, including uterine spiral artery (SA) remodeling to accommodate the fetus and provide nutrients and oxygen for the fetus to survive. Uterine spiral arteries transform from small-diameter, high-resistance arteries to large-diameter and low-resistance arteries during pregnancy. This transformation includes many changes, such as increased permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…These are branches of the uterine artery that will allow the adequate supply of nutrients and oxygen to the embryo. At the onset of placentation, uNKs promote a series of processes to transform these specific arteries, including: vessel dilatation, increased permeability, the progressive loss of endothelial cells, or phenotypic switching and migration of vascular smooth muscle cells [25][26][27] (Figure 1).…”
Section: The Role Of Natural Killer Cells In Early Pregnancymentioning
confidence: 99%
“…These are branches of the uterine artery that will allow the adequate supply of nutrients and oxygen to the embryo. At the onset of placentation, uNKs promote a series of processes to transform these specific arteries, including: vessel dilatation, increased permeability, the progressive loss of endothelial cells, or phenotypic switching and migration of vascular smooth muscle cells [25][26][27] (Figure 1).…”
Section: The Role Of Natural Killer Cells In Early Pregnancymentioning
confidence: 99%
“…The two-stage process of implantation and placental development involves maternal–fetal interaction and adaptation [ 53 , 54 ]. The changes in the syncytiotrophoblast, trophoblast, and uterine arteries are under the influence of uterine natural killer cells and regulatory T cells [ 55 , 56 ]. Angiogenic factors, such as the PlGF (placental growth factor) and sFLT (soluble fms-like tyrosine kinase-1) regulate placental angioneogenesis, vasculogenesis, and maternal circulatory adaption [ 57 ].…”
Section: Placenta-related Syndromesmentioning
confidence: 99%
“…It is well known that trophoblast cells are the origin of sFLT1 that enters the maternal circulation during pregnancy, leading to the hypothesis that abnormal trophoblast formation and therefore excess sFLT1 is the primary cause of maternal vascular dysfunction in this disease through its sequestration of VEGF [10]. Abnormal trophoblast invasion into the maternal decidua has been intensely studied in PE [11]. A recent single-cell transcriptomic study in human pregnancy revealed a cell-autonomous dysregulation of FLT1 and PLGF transcription in the syncytial trophoblast in early but not late preeclampsia [12].…”
Section: Introductionmentioning
confidence: 99%